Benchmarking on management system in manufacturing companies in establishing maintenance awareness - Mohd Faisal, Che Yusof (2008)
In manufacturing companies, gaining profit is the most obvious goal to be achieved. Many systems and application are being used by various international companies in improving their profit. Quality Management System (QMS) is among the system applied in achieving the goal of high maintenance awareness. This is because a good condition of the machines will give high productivity. Most of the companies are applying the recommendation based on the documentation to get the accreditation for ISO 9001:2000.This is significant to prove that the company is reliable and serves an international level of standards in their services. Companies are having their documentation on management of their own to observe the process executed and the weaknesses arise from the process. To be more advance, the maintenance awareness can be established in earlier stage such as in universities or college. This project is to benchmark the work applied by the companies in their process to maintain their status as an accredited company. It also a study to find a better systems and application that can be applied in the educational institution. To achieve the goal, every steps need to observed from the documentation until the production. The maintenance awareness will be observed and measured by using questionnaires sets and also interviews. With the lack of exposure to real working environment, the results show that respondents in an educational institution are able to have a higher maintenance awareness level than respondents in manufacturing companies.